A Comparative analysis of Bangladesh Water Management Practice with European Water Framework Directives - Alam, Md. Masud; Quevauviller, Philippe (Engineering International, 2013)
Until 90, water management plans in Bangladesh focused mainly to controlling floods and facilitates drainage and irrigation which were segregate plans, and  caused detrimental effects of other sectors such as water supply, sanitation, industry, fisheries plus environmental and other in-stream demands. For avoiding the fragmentation, the country has achieved a remarkable progress in Integrated Water Resources Management (IWRM) activities after the period of 90.The Flood Action Plan (FAP, 1989-1995) was the pioneer of IWRM plan in Bangladesh. In 1995, Government approved The Bangladesh Water and Flood Management Strategy (BWFMS) which was an outcome of FAP. Under the recommendation of BWFMS, Bangladesh prepared NWPo and NWMP which were the holistic and government approved documents for applying integrated water resources practice in Bangladesh.The European Union has a long experience for basin wide integrated water resources management within Europe. The European Parliament and the Council of the European Union established a framework for Community action in the field of water policy in 23 October 2000 European Union’s water policies such as the Water Framework Directive (2000/60/EC). The EU’s experience (including its 27 Member States) is based on the best scientific knowledge and available technologies. In particular, the Water Framework Directive (2000/60/EC) mainly focuses on river basin management rules and principles. It is recognized that the Water Framework Directive (WFD) might be used as an example for basin wide IWRM implementation and economic development for the developing countries like Bangladesh, taking into account their socio-economic conditions.This study will show that, how the European Union Water Framework Directive (WFD) model can be adapted for the effective implementation of integrated water resources in Bangladesh. A Common Implementation Strategy (CIS) has been depicted for sustainable IWRM in Bangladesh.
Keywords: Integrated Water Resources Management (IWRM); Common Implementation Strategy (CIS); Water Framework Directive (WFD)